CONSTRUCTIVIST PEDAGOGICAL FRAMEWORKS: INSIGHTS FROM SOCRATES, JEAN PIAGET, AND ROCKEFELLER - Marianus Ola Kenoba; Josef Kusi; Sisilia Helena Joaline Tadu Lado (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The practice of conventional education has reduced students to mere recipients of knowledge. This creates a dilemma of objectification for students in concrete learning experiences. Meanwhile, educators exercise full authority over the learning process, with the underlying assumption that an educator's knowledge represents an absolute truth. This paper aims to demonstrate the praxis model of constructivist pedagogy. This paper critically examines the transmission-based paradigm of education by proposing a dialogical and reflective approach to learning. Historically, this model can be traced back to the dialogical philosophy espoused by Socrates. In contemporary pedagogy, it is reflected in Jean Piaget's theory of constructivism and in the curriculum at Rockefeller University. This research employs a critical hermeneutics methodology. The results of the biographical analysis of the thoughts of Socrates, Jean Piaget, and the learning practices within the curriculum at Rockefeller University indicate that constructivist pedagogy represents an ideal type of humanist pedagogical praxis that is highly relevant to the modern education system. Accordingly, constructivist pedagogy provides a humanistic and dialogically grounded framework for learning, one that is well-suited to meet the evolving demands of 21st-century education.